Analysis of the (lymph-)angiogenic potential of regenerative scaffolds and the impact of adipose-derived mesenchymal stem cells - Koll, Katja K.; Klevansky, Donna A.; Kasakovski, Dimitri; Ahmadzadeh, Nima; Will-Marks, Patrick; Kneser, Ulrich; Hirche, Christoph (Plastic and reconstructive surgery, 2025)
Background: - Regenerative matrices are essential in the therapy of complex wounds, where lymphangiogenesis and angiogenesis play crucial roles. This work investigates the lymph and angiogenic potential of regenerative scaffolds and the influence of adipose-derived mesenchymal stem cells (ADSC) in a rodent wound model. -Methods: -In a wound model, the authors administered different acellular dermal matrices (ADMs) to 2 wounds on each rat—enriching 1 with ADSCs and leaving the other without. ADSCs were isolated from rodent inguinal fat tissue, characterized using fluorescence-activated cell sorting and their viability confirmed in vitro on different matrices. Tissue samples were collected on days 7, 14, 21, and 28 postoperatively. Six different ADMs, including 2 synthetic and 4 biological variants, were compared using histologic, immunofluorescence staining, and molecular biological analyses. -Results: -ADM integration varied, with collagen (COL)-elastin-ADM showing the highest integration (95%) and polyurethane (PU)-ADM, the lowest (23%) after 7 days. Synthetic ADMs, particularly PU-ADM, exhibited the highest mRNA expression of angiogenesis and lymphangiogenesis markers at 7 and 28 days. Protein analysis showed that synthetic ADMs had the highest CD31 levels from 14 to 28 days, whereas COL-ADM had the highest LYVE1 and PROX1 levels at 21 and 28 days. Immunofluorescence revealed polylactide-ADM consistently had the highest CD31 and LYVE1 signals at various times, with PU-ADM and COL-ADM peaking at 28 days. The application of ADSCs did not enhance lymphangiogenesis or angiogenesis. - Conclusions: - ADM material properties impact lymphangiogenesis and angiogenesis, guiding therapeutic selection and tissue regeneration. This study highlights COL-, polylactide-, and PU-ADMs as the most effective in promoting these processes. - Clinical Relevance Statement: - This study provides valuable insights into the unique material properties of ADMs, highlighting COL-, polylactide-, and PU-ADMs as exhibiting the most robust effects on lymphangiogenesis and angiogenesis.